Masquelet's induced membrane technique: Review of current concepts and future directions. Issue 4 (13th January 2021) - Alford, Andrea I.; Nicolaou, Daemeon; Hake, Mark; McBride‐Gagyi, Sarah
Abstract: Masquelet's induced membrane technique (MIMT) is a relatively new, two‐stage surgical procedure to reconstruct segmental bone defects. First performed by Dr. Masquelet in the mid‐1980s, MIMT has shown great promise to revolutionize critical‐sized bone defect repair and has several advantages over its alternative, distraction osteogenesis (DO). Also, its success in extremely challenging cases (defects > 15 cm) suggests that its study could lead to discovery of novel biological mechanisms that might be at play during segmental defect healing and fracture non‐union. MIMT's advantages over DO have led to a world‐wide increase in MIMT procedures over the past decades. However, MIMT often needs to be repeated and so the average initial success rate in adults lags significantly behind that of DO (86% vs 95%, respectively). The autologous foreign‐body membrane created during the first stage by the immune system's response to a polymethyl methacrylate bone cement spacer is critical to supporting the morselized bone graft implanted in the second stage. However, the biological and/or physical mechanisms by which the membrane supports graft to bone union are unclear. This lack of knowledge makes refining MIMT and improving the success rates through technique improvements and patient selection a significant challenge and hinders wider adoption. In this review, current knowledge from basic, translational, and clinical studies is summarized. The dynamics of both stages under normal conditions as well as with drug or material perturbations is discussed along with perspectives on high‐priority future research directions.